ANALYSING INDONESIAN’S NEW AND RENEWABLE ENERGY BILL IN TERMS OF A NON-NUCLEAR COUNTRY (NPT) - Raihan Maulana Putra; Sophia Listriani (Universitas Syiah Kuala, 2022)
This paper is explaining about the importance of the new energy bill to build and operating nuclear as a sustainable energy. This research is conducted using normative-juridical methods. The results have shown that there are many international aspects of nuclear law and regulations that have been adopted or ratified which needs to be accommodated in national legislation and many oppositions in the fear with the nuclear management failure and the past nuclear fatality and the lack of human resources; and also the effect on NPT has rather clear that the use of nuclear power for peaceful use is allowed for peace use and benefit. Suggestion on several implementing law and nuclear security regulations that have not been adequately regulated need to be prepared and the bill of new and renewable energy should be imposed as soon as possible and to conclude nuclear power in the bill..